1973
DOI: 10.1530/jrf.0.0330069
|View full text |Cite
|
Sign up to set email alerts
|

CONTINUOUS MEASUREMENT BY RADIO-TELEMETRY OF VAGINAL pH DURING HUMAN COITUS

Abstract: The use of the pH-pill has allowed continuous monitoring of vaginal pH during human coitus. In the case of a couple of normal fertility, there was an immediate buffering by seminal plasma so that the vaginal pH changed in 8 sec from pH 4\m=.\3to pH 7\m=.\2.In the case of a couple of low (male) fertility, the immediate effect of the arrival of semen in the vagina was a change from pH 3\m=.\5to pH 5\m=.\5.A similarly small change in pH occurred when the seminal volume of a fertile male subject had been depleted,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(76 citation statements)
references
References 14 publications
3
73
0
Order By: Relevance
“…It has long been known that following ejaculation, semen raises the normally acidic pH of vaginal fluid to 7.0 or higher within 30 s, and this neutralization of the vaginal lumen can persist for at least 2 hrs. 61,62 The buffering capacity of semen may help to maintain conditions that are conducive to HIV-1 stability and infection. [63][64][65][66] 72 Furthermore, complement activation in seminal fluid generates C3 cleavage and augments HIV-1 infection in epithelial cells.…”
Section: 58mentioning
confidence: 99%
“…It has long been known that following ejaculation, semen raises the normally acidic pH of vaginal fluid to 7.0 or higher within 30 s, and this neutralization of the vaginal lumen can persist for at least 2 hrs. 61,62 The buffering capacity of semen may help to maintain conditions that are conducive to HIV-1 stability and infection. [63][64][65][66] 72 Furthermore, complement activation in seminal fluid generates C3 cleavage and augments HIV-1 infection in epithelial cells.…”
Section: 58mentioning
confidence: 99%
“…48 Masters 49 had previously made similar measures, but he placed the electrode blindly into the vagina and did not undertake any statistical analysis of his data. A study using a radiotelemetry pH electrode placed high up in the fornix in just one subject 50 did not find any change in pH during coitus to orgasm. As a result of this, they questioned the hypothesis that the lubrication fluid formed on the surface of the vagina at arousal was a transudate of plasma as they assumed that the pH should have become neutralised to pH 7.…”
Section: +mentioning
confidence: 92%
“…The f 1 and f 2 values (46) are calculated using Eqs. (9) and (10), respectively, and shown in Table III. The results indicated that there was a significant difference between the HA degradation and drug release kinetics from HA-gel and HANPs either in the presence and absence of HAase.…”
Section: Kinetics Of Enzymatic Degradation and In Vitro Drugmentioning
confidence: 99%
“…The CV pH is also significantly higher (6 to 7) during the menstruation cycle (9). During sexual intercourse, the CV fluid is neutralized (pH 7 to 7.2) by the alkaline pH (7.2 to 8) of human semen within 8 s of arrival of seminal fluid (8,10). A small amount of semen is sufficient to neutralize the acidic pH of CV fluid due to its higher buffer capacity (8).…”
Section: Introductionmentioning
confidence: 99%